From Authenticity to Consumption: The Commodification of Intangible Heritage in the Cultural Tourism Economy: A Critical Approach in Light of the Frankfurt School - Benoumessad, Rabia Rayane; Charrouf, Mohamed (Journal of Ecohumanism, 2026)
The study analyzes the transformation of intangible cultural heritage within the cultural tourism economy, with a focus on processes of commodification and cultural reconfiguration, It adopts a critical approach grounded in the Frankfurt School, particularly the concept of the “Cultural Industry” developed by Adorno and Horkheimer, to examine how living cultural practices are turned into consumable and market-oriented products, The study concludes that, despite dominant narratives of preservation and development, cultural tourism often leads to the standardization and simplification of heritage under market logic and tourist expectations, Authenticity is understood as a socially constructed and dynamic concept that is continuously reshaped within tourism contexts, Ultimately, the relationship between intangible cultural heritage and cultural tourism is characterized by a structural tension between cultural preservation and economic rationalization, whereby capitalist logic contributes to transforming heritage into a commodified cultural good.